Efficacy of B Lynch Suture and Intrauterine Balloon Tamponade Among Women with Severe Postpartum Hemorrhage Presenting to MMC Mardan - Akhtar, Tayyaba; Mahmood, Sadia; Jamal, Sundas; Amin, Nuzhat (Indus Journal of Bioscience Research, 2025)
Background: Severe postpartum hemorrhage (PPH) is a common cause of maternal morbidity and mortality and requires effective, timely interventions. Two well-known methods in the control of PPH include the B Lynch suture and the intrauterine balloon tamponade, although the comparative effectiveness between the two is yet to be determined. Objective: To compare the efficacy b lynch suture and intrauterine balloon tamponade among women with severe postpartum hemorrhage presenting to MMC Mardan. Study Design: A randomized controlled trial. Duration and Place of Study: The study was conducted from September 2024 to March 2025 at the Department of Obstetrics and Gynecology, Mardan Medical Complex, Mardan. Methodology: A total of 152 women with severe postpartum hemorrhage were enrolled and randomly assigned to either the B Lynch suture group (Group A) or the intrauterine balloon tamponade group (Group B). Demographic and clinical data were collected, and the effectiveness of each technique was evaluated based on the cessation of bleeding within 15 minutes. The primary outcomes measured included the success rate of each intervention. Results: The primary efficacy analysis revealed that the B Lynch suture was successful in 68 patients (89.5%), while intrauterine balloon tamponade succeeded in 60 patients (78.9%). However, this difference did not achieve statistical significance (p=0.075). Conclusion: While B Lynch suture demonstrated a numerically higher success rate in controlling severe postpartum hemorrhage compared to intrauterine balloon tamponade, the difference did not reach statistical significance.